PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN RASA INGIN TAHU (CURIOSITY) SISWA KELAS X MIPA 2 SMA NEGERI 6 SURAKARTA TAHUN PELAJARAN 2015/2016 - Latiifani, Choirunnisa; Rinanto, Yudi; Marjono, Marjono (BIO-PEDAGOGI, 2016)
The research aimed to enhance student curiosity by implementation of guided inquiry learning model at grade X MIPA 2 SMA N 6 Surakarta academic year 2015/2016 amount of 30 student comprise of 18 male and 12 female. This research was a Classroom Action Research that performed within 3 cycles. Each cycle consisted of 4 steps; planning, action, observation, and reflection. Data were obtained by observation, test, interview, and documentation. Student’s curiosity assessed by observation and questionnaire. The data were analyzed by qualitative descriptive technique. The result showed that the student’s curiosity were increased in precycle, cycle I, cycle II, and cycle III. Student who actively ask increased from 15,33 % to 54 %. Student who paid attention to do experiment increased from 40,67 % to 80,67 %. Student who interested to do experiment increased from 24,00 % to 60 %, and student who made a note and summarized increased from 37,33 % to 54 %. Conclusion of the research is that implementation of Guided Inquiry Learning Model can enhance curiosity of student in X MIPA 2 SMA Negeri 6 Surakarta academic year 2015/2016. Keywords: Curiosity, Guided Inquiry Learning